PENGGUNAAN EKSTRAK BIJI BUAH PINANG (Areca catechu L.) UNTUK MEMPERPANJANG WAKTU SIMPAN IKAN KEMBUNG (Rastrelliger catagurna) TAHUN 2013 - vina anggina; wirsal hasan; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
Seeds areca extract (Areca catechu L.) was result of percolation of Seeds areca. Seeds areca extract (Areca catechu L.) could be used as natural preservative. Areca seed extract contains polyphenols which delay the growth of microbial spoilage. The purpose of this study was to determine the ability of Areca seeds extract (Areca catechu L.) in extending the shelf life of mackerel (Rastrelliger catagurna). This study used quasi experiment with Pre and Post Test Design. The object of this research was mackerel. This experiment was conducted with four treatments: without immersion (control), immersion using areca seed extract with a concentrations of 0,5%, 1%, 1,5%, and 2% in 1 L of water and any treatment carried out four repetations. The average preserving time of mackarel at concentrations 0%, which is 5 hours 45 minutes, a concentrations 0,5% which is 7 hours 45 minutes, the concentrations of 1% 9 hours 15 minutes, the concentrations of 1,5% which is 9 hours 37 minutes, and the concentrations 2% that is 10 hours 37 minutes. The result of this study showed that there were differences in durability mackerel without soaking and after soaking Areca seeds extract. The results showed that the durability of mackerel without soaking and soaking the fish were given seeds areca extract at different concentrations. Mackerel using seeds areca extract 2% produces the most durable fish, but has a bitter taste after being fried. While the mackerel using seeds areca extract 1% had retentiontime not too long, but do not have a bitter taste when fried, and fish without soaking faster slimy and foul smelling Keyword: Areca (Areca catechu L.), mackerel fish (Rastrellinger catagurna), Preservative.